2017
DOI: 10.1038/s41598-017-10345-7
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and richness of aphid parasitoid wasps in cotton fields in northern China

Abstract: The cotton aphid, Aphis gossypii (Hemiptera: Aphididae), is a serious pest of cotton across the globe, particularly in the cotton agroecosystems of northern China. Parasitic wasps are deemed to be important natural enemies of A. gossypii, but limited information exists about their species composition, richness and seasonal dynamics in northern China. In this study, we combine sampling over a broad geographical area with intensive field trials over the course of three cropping seasons to describe parasitoid-hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 37 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…communis , is known to attack various aphids in different crops across many countries and regions [ 53 56 ]. Yang et al [ 57 ] reported that among wasps emerged from mummies in northern China, B . communis accounted for most (>93%) of the primary parasitoids of A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…communis , is known to attack various aphids in different crops across many countries and regions [ 53 56 ]. Yang et al [ 57 ] reported that among wasps emerged from mummies in northern China, B . communis accounted for most (>93%) of the primary parasitoids of A .…”
Section: Discussionmentioning
confidence: 99%
“…aphidis and species of Syrphophagus were the dominant parasitoids proportionally, which is similar to the results found in northern China with A . gossypii [ 57 ]. Some other species of hyperparasitoids, such as D .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the aphid species, R. maidis could be used as an alternative host for the reproduction of the parasitoid L. testaceipes on sorghum [33] . In northern China, three primary parasitoid species and 12 hyperparasitoids on A. gossypii were recorded in cotton fields [15] , while three parasitoids and 15 hyperparasitoids were collected in wheat fields [32] .…”
Section: The Distribution Of Parasitic Wasps Is Almost Nationwide DImentioning
confidence: 99%
“…Cereal aphids are subject to parasitism rates of 30-80% on Danish and New Zealand winter wheat, mostly from Aphidius ervi Haliday and Aphidius rhopalosiphi (De Stefani-Perez [14] . In northern China, two primary parasitoid species and ten different hyperparasitoid species were collected in cotton fields [15]. In another study, three primary parasitoid species were found, and the hyperparasitoid guild was more diverse, consisting of 14 species [15,16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation